(untitled) (Research, Society and Development, 2023)
The aim of the present study was to review the impacts of the anti-vaccine movement in the fight against the COVID-19 pandemic in Brazil in the scientific literature. A descriptive narrative review of publications from the years 2020, 2021 and 2022 was carried out, applying inclusion and exclusion criteria that resulted in the selection of seven articles for the construction of this study. The most prominent contexts are related to the speeches of federal government leaders, dissemination of false news, distorted contexts of news and studies by enlightened groups in society, especially health professionals and support from public authorities and professional societies that disseminated untruths regarding the COVID-19 vaccine. Raising awareness through lectures, reports, bulletins, quality journalism that reaches the most remote locations, public health education policies, effective clarification of health professionals in their relationship with the patient, are important actions that help to combat false information and can help to weaken the anti-vaccination movement, being able to raise the protection indexes of all age groups again, fighting important diseases and drastically reducing the negative impacts of the actions of these groups.